2008
DOI: 10.1074/jbc.m802917200
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism Governing the Oncogenic Potential of SOX2 in Breast Cancer

Abstract: SOX genes encode a family of high-mobility group transcription factors that play critical roles in organogenesis. The functional specificity of different SOX proteins and the tissue specificity of a particular SOX factor are largely determined by the differential partnership of SOX transcription factors with other transcription regulators, many of which have not yet been discovered. Virtually all members of the SOX family have been found to be deregulated in a wide variety of tumors. However, little is known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
301
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(332 citation statements)
references
References 42 publications
27
301
2
2
Order By: Relevance
“…To investigate this issue we examined the presence of stem-like cells by assessing the expression of the major stem cell pluripotency regulators, Oct4, Sox2 and Nanog (Jaenisch and Young, 2008), in human natural breast tumours. We observed that Sox2 is expressed at the protein level in breast tumours, as expected (RodriguezPinilla et al, 2007;Chen et al, 2008). However, Sox2 expression was more prevalent in the early stages of tumour development and in the ductal areas of tumours that still showed intact ductal structures, as is the case of lung cancer (Sholl et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…To investigate this issue we examined the presence of stem-like cells by assessing the expression of the major stem cell pluripotency regulators, Oct4, Sox2 and Nanog (Jaenisch and Young, 2008), in human natural breast tumours. We observed that Sox2 is expressed at the protein level in breast tumours, as expected (RodriguezPinilla et al, 2007;Chen et al, 2008). However, Sox2 expression was more prevalent in the early stages of tumour development and in the ductal areas of tumours that still showed intact ductal structures, as is the case of lung cancer (Sholl et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…27 Chen et al 28 These observations indicate that SOX2 has a role in tumorigenicity of both gliomas and lung adenocarcinomas in vivo; however, its exact molecular mechanisms are still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In this regard, SOX2, a member of the SRYrelated HMG-box family of transcription factors, has mainly been studied in embryonic stem cells and in reprogramming of adult somatic cells to a pluripotent stem cell state, and it has been recently recognized to promote aberrant stem cell selfrenewal signaling in breast cancer. [5][6][7] First, normal breast tissues express low levels of SOX2, but SOX2 in early-stage breast carcinomas is differentially reactivated in the ductal areas of tumors that still show intact ductal structures, which strongly suggests that SOX2 may be expressed during the initial phases of tumorigenesis. However, SOX2 is lost as the tumor progresses toward advanced stages.…”
Section: T He Restoration Of Pluripotency Cir-mentioning
confidence: 99%